β- and γ-Actins in the nucleus of human melanoma A375 cells - Migocka-Patrzałek, Marta (Histochem Cell Biol, 2015)
Actin is a highly conserved protein that is expressed in all eukaryotic cells and has essential functions in the cytoplasm and the nucleus. Nuclear actin is involved in transcription by all three RNA polymerases, chromatin remodelling, RNA processing, intranuclear transport, nuclear export and in maintenance of the nuclear architecture. The nuclear actin level and polymerization state are important factors regulating nuclear processes such as transcription. Our study shows that, in contrast to the cytoplasm, the majority of endogenous nuclear actin is unpolymerized in human melanoma A375 cells. Most mammalian cells express the two non-muscle β- and γ-actin isoforms that differ in only four amino acids. Despite their sequence similarity, studies analysing the cytoplasmic functions of these isoforms demonstrated that β- and γ-actins show differences in localization and function. However, little is known about the involvement of the individual actin isoforms in nuclear processes. Here, we used the human melanoma A375 cell line to analyse actin isoforms in regard to their nuclear localization. We show that both β- and γ-non-muscle actin isoforms are present in nuclei of these cells. Immunolocalization studies demonstrate that both isoforms co-localize with RNA polymerase II and hnRNP U. However, we observe differences in the ratio of cytoplasmic to nuclear actin distribution between the isoforms. We show that β-actin has a significantly higher nucleus-to-cytoplasm ratio than γ-actin. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00418-015-1349-8) contains supplementary material, which is available to authorized users.